Evolutionary, genomic, and biogeographic characterization of two novel xenobiotics-degrading strains affiliated with Dechloromonas. Issue 6 (June 2021) - Zhang, Shuangfei; Amanze, Charles; Sun, Chongran; Zou, Kai; Fu, Shaodong; Deng, Yan; Liu, Xueduan; Liang, Yili
Abstract: Xenobiotics are generally known as man-made refractory organic pollutants widely distributed in various environments. For exploring the bioremediation possibility of xenobiotics, two novel xenobiotics-degrading strains affiliated with Azonexaceae were isolated. We report here the phylogenetics, genome, and geo-distribution of a novel and ubiquitous Azonexaceae species that primarily joins in the cometabolic process of some xenobiotics in natural communities. Strains s22 and t15 could be proposed as a novel species within Dechloromonas based on genomic and multi-phylogenetic analysis. Pan-genome analysis showed that the 63 core genes in Dechloromonas include genes for dozens of metabolisms such as nitrogen fixation protein ( nifU ), nitrogen regulatory protein ( glnK ), dCTP deaminase, C4-dicarboxylate transporter, and fructose-bisphosphate aldolase. Strains s22 and t15 have the ability to metabolize nitrogen, including nitrogen fixation, NirS -dependent denitrification, and dissimilatory nitrate reduction. Moreover, the novel species possesses the EnvZ-OmpR two-component system for controlling osmotic stress and QseC-QseB system for quorum sensing to rapidly sense environmental changes. It is intriguing that this new species has a series of genes for the biodegradation of some xenobiotics such as azathioprine, 6-Mercaptopurine, trinitrotoluene, chloroalkane, and chloroalkene. Specifically, glutathione S-transferase ( GST ) and 4-oxalocrotonate tautomerase ( praC ) in this novel species play important roles in the detoxification metabolism of some xenobiotics like dioxin, trichloroethene, chloroacetyl chloride, benzo[a]pyrene, and aflatoxin B1. Using data from GenBank, DDBJ and EMBL databases, we also demonstrated that members of this novel species were found globally in plants (e.g. rice), guts (e.g. insect), pristine and contaminated regions. Given these data, Dechloromonas sp. strains s22 and t15 take part in the biodegradation of some xenobiotics through key enzymes. Abstract : Dechloromonas ; Xenobiotics biodegradation; Comparative genomics; Novel species; Biogeographic distribution.